(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
In the early Nineties, on the wave of the enthusiasm for the technological revolution that in the same years saw the advent of computers, the first Net Artists embraced hacktivism and the World Wide Web of Berners-Lee as means of free and unlimited sharing, a way to make art outside of the collecting dynamics, to elude the system, including the art system. This will radically revolutionize the concepts of author, user and originality of the work, ideally leading to a new conception of art as a primary good, accessible at any time to anyone who has a device and an Internet connection. By first delving into the theoretical and ideological aspects that makes early Net Art one of the most revolutionary and politically active art forms, we will face artivism in the works of Net Artists such as Vuk Ćosić, Ubermongen, 0100101110101101.org, analyzing the revolutionary impact left in heritage to contemporary culture.